2015
DOI: 10.1038/srep14122
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in corticospinal excitability when seeing fearful body expressions

Abstract: Quick inhibition of approach tendencies in response to signals of potential threats is thought to promote survival. However, little is known about the effect of viewing fearful expressions on the early dynamics of the human motor system. We used the high temporal resolution of single-pulse and paired-pulse transcranial magnetic stimulation (TMS) over the motor cortex to assess corticospinal excitability (CSE) and intracortical facilitation (ICF) during observation of happy, fearful and neutral body postures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 61 publications
4
91
0
Order By: Relevance
“…Admittedly, there is a clear distinction between the perception of angry expressions, as examined in the present study, and the experience of anger, which was not assessed here. Notably, however, the coherence between the structures found here and those reported in prior findings addressing anger experience is in keeping with the view that neural systems related to the perception of emotional signals, on the one hand, and to the expression and experience of the same emotion, on the other, largely overlap47497879808182. Whether amygdala PPI varies similarly during perception with or without experience of the same emotion awaits future investigation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Admittedly, there is a clear distinction between the perception of angry expressions, as examined in the present study, and the experience of anger, which was not assessed here. Notably, however, the coherence between the structures found here and those reported in prior findings addressing anger experience is in keeping with the view that neural systems related to the perception of emotional signals, on the one hand, and to the expression and experience of the same emotion, on the other, largely overlap47497879808182. Whether amygdala PPI varies similarly during perception with or without experience of the same emotion awaits future investigation.…”
Section: Discussionsupporting
confidence: 87%
“…The coupling of amygdala and motor areas outlines the influence of different emotions in fostering action preparation and planning, as well as motor resonance. In fact, observing emotional stimuli increases motor excitability relative to neutral images8182104 and may reflect approach and avoidance preparation105, motor mimicry and emotional contagion484954106107108109110. Such functional interaction is consistent with the anatomical evidence indicating white matter connectivity between the amygdala and the motor regions in nonhuman primates111 and humans112.…”
Section: Discussionsupporting
confidence: 77%
“…Based on previous research (Oliveri et al, ; Schutter et al, ), we stimulated the motor cortex 300 ms poststimulus onset and found a selective increase for angry bodily expressions. Interestingly, Borgomaneri, Gazzola, & Avenanti () showed that at 150‐ms poststimulus onset, motor corticospinal excitability increased only for stimuli negative in valence, while at 300‐ms poststimulus onset, it increased for both stimuli negative and positive in valence (Baumgartner et al, ; see also Borgomaneri et al, ; Borgomaneri, Vitale et al, ; Coombes et al, ; Hajcak et al, ). In contrast, Schutter and colleagues (2008) found that fearful, but not happy or neutral faces increased motor corticospinal excitability as measured at 300 ms after stimulus onset.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not conduct a formal power analysis, we decided to test at least 16 participants based on previous studies that used single‐pulse TMS to investigate emotion processing. For these studies, the mean number of participants reported is 15.08 with a standard deviation of 4.83, with a minimum of seven participants and a maximum of 24 participants, well suited to find medium to large effect sizes (Avenanti et al, ; Avenanti, Minio‐Paluello, Bufalari, & Aglioti, ; Avenanti, Minio‐Paluello, Sforza, & Aglioti, ; Baumgartner et al, ; Borgomaneri et al, ; Borgomaneri, Gazzola, & Avenanti, ; Borgomaneri, Vitale, & Avenanti, ; Borgomaneri, Vitale, Gazzola, & Avenanti, ; Coelho et al, ; Coombes et al, ; Enticott et al, ; Fadiga et al, ; Giovannelli et al, ; Hajcak et al, ; Overeem et al, ; Schutter et al, ; van Loon et al, ). Eighteen healthy right‐handed volunteers (14 women, four men), aged between 18 and 24 years, participated in exchange for course credits or payment.…”
Section: Methodsmentioning
confidence: 99%
“…These findings converge with the notion that emotion processing with and without stimulus awareness co-exist and interact in the intact brain, though they can be dissociated because of focal brain damage or experimental manipulation. Additional evidence on the motor influence of emotion perception is provided by transcranial magnetic stimulation (TMS) studies (Borgomaneri et al, 2015a,b). Although these studies did not manipulate directly visual awareness, they found extremely rapid sensory-motor modulation in response to fearful bodily expressions, supposedly underlying freezing mechanisms.…”
Section: Consequences Of Amg Activity During Non-conscious Emotion Pementioning
confidence: 99%